Stretchable conductors made of single wall carbon nanotubes self-grafted on polymer films. (May 2020) - Fazi, L; Prioriello, A; Scacco, V; Ciccognani, W; Serra, E; Mirabile Gattia, D; Morales, P; Limiti, E; Senesi, R
Abstract: Aiming at the accomplishment of stretchable and elastic conductive devices, we report in this work electrical, mechanical and thermal characterization of a composite conductive material obtained by self-grafting of single wall carbon nanotubes bundles on different polymeric films. The dependence of resistance of micrometric composite conductors on the applied strain was measured; the current breakdown threshold was also measured together with the corresponding temperature increase. Finally, the dependence of an AC signal attenuation for a bi-layer single wall carbon nanotubes conductor sandwiching a 25 μm thick poly-ethylene film was obtained as a function of the signal frequency, and the experimental results were satisfactorily compared to a simple RLC model.